MONITORING AND ANALYSIS OF ACADEMIC PERFORMANCE AT UNIVERSITY BY MEANS OF SOCIAL NETWORKING SERVICES - Pivneva, Svetlana; Vitkovskaya, Nataliaya; Sergeevna Sizova, Yulia; Nikolaevna Gorlacheva, Evgeniya (Revista Inclusiones, 2019)
Improvement of the education system increasingly depends on the effective management of the quality of education. The article presents the possibilities of monitoring and analyzing the quality of knowledge in higher education institutions students by means of social networking services and social media. Based on an expert survey, the advantages and disadvantages of using the means of social networking services for conducting various types of monitoring are identified, the key advantages of using the means of social networking services designed for analyzing the quality of knowledge acquisition are emphasized, a comparative analysis of social networking services in various types of monitoring is conducted, and examples of the use of the means of various social networking services are provided.